Safety of Lumbar Puncture Procedures in Patients with Alzheimer's Disease - Peskind, E. (2009)
Changes in cerebrospinal fluid (CSF) biomarkers are representative of biochemical changes in the brain. Collection of CSF by lumbar puncture (LP) is essential for biomarker analysis, which is important for research in neurodegenerative disorders. However, LP for research purposes has been controversial due to a reported high incidence of severe LP headache when using standard 18g or 20g Quincke needles with a beveled cutting tip. A procedural safety analysis was performed using the database of a multicenter, 13-week study of CSF cholinesterase activity. A 24g Sprotte atraumatic needle was used to collect CSF at baseline and at Week 13 from 63 older patients with mild to moderate Alzheimer's disease. There was a < 2% LP headache incidence, and a favorable safety profile was reported. In conclusion, LP performed with a 24g Sprotte atraumatic needle (blunt, “bullet” tip) was a well-tolerated procedure, with good acceptability.